The relationship of sports me dia to achievement motivation among soccer players in Syrian university teams (Applied study) - طلال الفرا, عمار; محمود, بلال (Latakia University Journal -Medical Sciences Series, 2022)
This study aimed to show the role of sports media in improving the motivation of sports achievement among football players participating in university tournaments. The research relied on the descriptive analytical method, and the study community represented the football players in the university football championships, and the study sample consisted of 80 players from the teams of the Syrian universities. The study concluded that there is a positive and morally significant correlation between sports media and the motivation to achieve success among football players participating in university tournaments, in addition to the existence of a positive and morally significant relationship between sports media and the motivation to avoid failure among football players participating in university tournaments, as well. It was found that there is a positive correlation with a moral significance between the sports media and the motivation for sports achievement among the football players participating in the university tournaments, and it is a positive relationship. This study also recommended the need to establish a media channel for university football tournaments, in addition to holding talk shows and seminars for university football tournaments on a regular and monthly basis.